2019
DOI: 10.3390/ijerph16040527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intervention Program Prev@cib on Traditional Bullying and Cyberbullying

Abstract: Due to the negative consequences of being bullied and the increase in cyberbullying among adolescents, there is a need for evidence-based programs to prevent and intervene in these types of peer violence. The aim of this study was to evaluate the effectiveness of the Prev@cib bullying and cyberbullying program, drawing on three theoretical frameworks: the ecological model, empowerment theory, and the model of personal and social responsibility. The Prev@cib program was evaluated using a repeated-measures pre-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 65 publications
3
69
0
7
Order By: Relevance
“…In this regard, Raskauskas and Stolz (2007) show that almost all (93%) of the adolescents bullied through ICTs present depressive symptoms. Regarding the relationship found between cyberbullying victimization and perceived stress, this may be due to cybervictims' high level of constant alertness due to the inability to escape the cybernetic bullying and control their lives (Kowalski, Giumetti, Schroeder, & Lattanner, 2014;Ortega-Barón, Buelga, Ayllón, Martínez-Ferrer, & Cava, 2019). In fact, in a very interesting study, González-Cabrera, Calvete, León-Mejía, Pérez-Sancho, and Peinado (2017) found that victims of cyberbullying present high levels of secretion of the stress hormone (cortisol), which seems to confirm the constant level of activation that occurs as a consequence of cyberbullying.…”
Section: Discussionmentioning
confidence: 85%
“…In this regard, Raskauskas and Stolz (2007) show that almost all (93%) of the adolescents bullied through ICTs present depressive symptoms. Regarding the relationship found between cyberbullying victimization and perceived stress, this may be due to cybervictims' high level of constant alertness due to the inability to escape the cybernetic bullying and control their lives (Kowalski, Giumetti, Schroeder, & Lattanner, 2014;Ortega-Barón, Buelga, Ayllón, Martínez-Ferrer, & Cava, 2019). In fact, in a very interesting study, González-Cabrera, Calvete, León-Mejía, Pérez-Sancho, and Peinado (2017) found that victims of cyberbullying present high levels of secretion of the stress hormone (cortisol), which seems to confirm the constant level of activation that occurs as a consequence of cyberbullying.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding cyber-aggression victimization, the main predictor variables were physical and relational offline DV victimization for both boys and girls. The close link between physical offline DV and cyber-aggression observed in this study highlights the ease with which adolescents transfer aggression from the real world to the virtual world, and both aggression toward peers and aggression toward romantic partners [2,6,16,28,58,67,68]. Physical offline DV involves intentionally using physical force to harm victims, e.g., hitting, pushing and slapping, while cyber-aggressions includes behaviors that involve harming victims through direct attacks, e.g., threats, insults or disseminating private information [1,11,20,21,38].…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, prevention/intervention professionals should evaluate a wide range of victimization types when they are presented with a specific incident and should incorporate this knowledge into their practical responses. Although many national and international programs are being run to reduce bullying victimization in young people [66][67][68], it is still unclear what techniques and programs would be effective in reducing poly-bullying victimization due to the limited studies on this phenomenon. In order to reduce negative correlates on mental health, interventions to promote resilience by developing social and emotional competencies should be considered in addition to the aforementioned programs against bullying [69][70][71].…”
Section: Discussionmentioning
confidence: 99%